2015
DOI: 10.1021/acschemneuro.5b00262
|View full text |Cite
|
Sign up to set email alerts
|

Direct High Affinity Interaction between Aβ42 and GSK3α Stimulates Hyperphosphorylation of Tau. A New Molecular Link in Alzheimer’s Disease?

Abstract: Amyloid β peptide (Aβ42) assemblies are considered central to the development of Alzheimer’s disease, but the mechanism of this toxicity remains unresolved. We screened protein microarrays with on-pathway oligomeric Aβ42 to identify candidate proteins interacting with toxic Aβ42 species. Samples prepared from Alexa546-Aβ42 and Aβ42 monomers at 1:5 molar ratio were incubated with the array during a time window of the amyloid fibril formation reaction during which the maximum number of transient oligomers exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…A binding affinity in the low nanomolar range has been calculated using surface plasmon resonance for Aβ1-42 interaction with the major intracellular target tau [27]. Noteworthy, the Aβ1-42 dissociation constant from Aβ-CaM complex is nearly identical to the reported dissociation constant of Aβ from PrP c [28], a cellular prion protein that has been proposed to mediate Aβ-induced synaptic dysfunction in the mouse brain [25], and also from glycogen synthase kinase 3α (GSK3α), a kinase that mediates hyperphosphorylation of tau and that it is stimulated in vitro by Aβ1-42 [29]. Alzheimer's disease modulated by calmodulin [8; 9; 11] and the major role of calmodulin-binding proteins in neuronal plasticity and activity [7; 8], it is likely that the interaction between Aβ and Ca 2+ /CaM will have major functional consequences for brain physiology.…”
Section: Discussionsupporting
confidence: 58%
“…A binding affinity in the low nanomolar range has been calculated using surface plasmon resonance for Aβ1-42 interaction with the major intracellular target tau [27]. Noteworthy, the Aβ1-42 dissociation constant from Aβ-CaM complex is nearly identical to the reported dissociation constant of Aβ from PrP c [28], a cellular prion protein that has been proposed to mediate Aβ-induced synaptic dysfunction in the mouse brain [25], and also from glycogen synthase kinase 3α (GSK3α), a kinase that mediates hyperphosphorylation of tau and that it is stimulated in vitro by Aβ1-42 [29]. Alzheimer's disease modulated by calmodulin [8; 9; 11] and the major role of calmodulin-binding proteins in neuronal plasticity and activity [7; 8], it is likely that the interaction between Aβ and Ca 2+ /CaM will have major functional consequences for brain physiology.…”
Section: Discussionsupporting
confidence: 58%
“…Tau has been proved to play a significant role in Alzheimer’s disease 6. In addition, the abnormal expression of tau protein was previously reported in many cancers, and the role of tau in cancer treatment has also been reported by others, such as gastric carcinoma,13,14 breast cancer,12,15,16 and ovarian cancer 9,17…”
Section: Discussionmentioning
confidence: 82%
“…In the previous studies, tau can interact with Fyn and with Pin1 and both the interactions have been thought to be associated with Alzheimer’s disease 5. Moreover, direct interaction between Aβ42 and GSK3α facilitates hyperphosphorylation of tau and this mechanism may be a new molecular signaling link in Alzheimer’s disease 6. What’s more, in prostate cancer, overexpression of tau was markedly associated with lower Gleason score, indicating that tau may be a potential prognostic marker in prostate cancer 7.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies have identified a series of microscopic steps in the process of aggregation that together contribute to the overall macroscopic kinetic profile of the reaction and have revealed the importance of the catalytic conversion of monomeric species into aggregates as a result of secondary nucleation on fibril surfaces. This process results in the production of neurotoxic oligomeric species (20,21) with distinct intracellular targets (29).…”
Section: Discussionmentioning
confidence: 99%